Implementation of a multi-level Power Electronic Inverter library in Modelica - Hill, Chris; Giangrande, Paolo; Gerada, C.; Bozhko, Serhiy (2014)
This paper presents a newly developed Power Electronic Inverter library in Modelica. The library utilises a multi-level approach with increasing model complexity at progressively higher levels. All levels are fully interchangeable so as to provide a flexible library able to be utilised for investigation at single or multiple levels of complexity. Within this inter¬changeable multi-level approach, there are two key attributes which are implemented into this new library. The first is the ability to include losses between the input and output of the Power Electronic Inverter. This is implemented so that the losses are included irrespective of the direction of power flow. Secondly, this library also provides the ability to trigger single or multiple open and short circuit faults within the Inverter. The library therefore provides an extremely useful tool able to compare system response under a variety of operational scenarios.